Training during the recession - Felstead, Alan [Verfasser]; Green, Francis [Verfasser] (My University, 1994)
"It is the conventional wisdom to assume that in the 'market model' of training found in Britain, training tends to be curtailed in recessions. Yet national level evidence shows only a small reduction in training during the recession of the early 1990s. Analysis of a survey of employers' training behaviour shows that a combination of regulations and the forces of market competition held up training activity or increased it in many companies. Many regulations were providing a floor for training activity, while the recession- intensified competition meant that firms had increasingly to fly flag of 'quality' in order to retain or expand their market share. The training requirements of the BS 5759 were widely cited. It is thus somewhat ironic that the 'market model' seems to have survived the recession as much through intervention as through the decisions of individual employers. It is more accurate to describe Britain's vocational training system as an 'employer-led model'." (author's abstract, IAB-Doku) ((en)) In dem Beitrag wird der Frage nachgegangen, wie sich die Rezession zu Beginn der 90er Jahre in Grossbritannien auf das betriebliche Weiterbildungsverhalten ausgewirkt hat. Es zeigt sich, dass entgegen den Erwartungen das Weiterbildungsangebot aufrechterhalten und in manchen Unternehmen sogar gesteigert wurde. (IAB)
Keywords: G 2.1.1 Ökonomie / Märkte; S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; I 2.2.1 Westeuropa; Rezession; Betriebliche Weiterbildung; Bildungsinvestition; Quantitative Angaben; Großbritannien; 1990-1992